2014
DOI: 10.1038/eye.2014.174
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of topical cyclosporine A 0.05% (Restasis) in long-standing prosthetic eye wearers: a pilot study

Abstract: Purpose Long-standing prosthetic eye wearing induces ocular surface inflammation. We investigated the short-term effects of topical cyclosporine A 0.05% (Restasis) in patients with ocular discomfort resulting from long-standing prosthetic eye wearing. Methods This was a prospective, interventional case series. Patients who were unilateral prosthetic eye wearers over a period of 5 years were enrolled at a single institution from March to July 2013. The subjects were instructed to instill topical cyclosporine A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 27 publications
0
14
0
3
Order By: Relevance
“…Discomfort can be interpreted in multiple ways: it encompasses discharge; pain; ocular fatigue; foreign body sensation; dryness; sticky sensation; tearing; itching; burning; heavy sensation; excessive blinking and uncomfortability in windy or very dry conditions (Han et al 2014). Discomfort can be interpreted in multiple ways: it encompasses discharge; pain; ocular fatigue; foreign body sensation; dryness; sticky sensation; tearing; itching; burning; heavy sensation; excessive blinking and uncomfortability in windy or very dry conditions (Han et al 2014).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Discomfort can be interpreted in multiple ways: it encompasses discharge; pain; ocular fatigue; foreign body sensation; dryness; sticky sensation; tearing; itching; burning; heavy sensation; excessive blinking and uncomfortability in windy or very dry conditions (Han et al 2014). Discomfort can be interpreted in multiple ways: it encompasses discharge; pain; ocular fatigue; foreign body sensation; dryness; sticky sensation; tearing; itching; burning; heavy sensation; excessive blinking and uncomfortability in windy or very dry conditions (Han et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that articles frequently reported 'discomfort' when describing patient symptoms. Discomfort can be interpreted in multiple ways: it encompasses discharge; pain; ocular fatigue; foreign body sensation; dryness; sticky sensation; tearing; itching; burning; heavy sensation; excessive blinking and uncomfortability in windy or very dry conditions (Han et al 2014). We excluded articles that reported patients having discomfort.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations